Description of the Level of Knowledge and Behavior of Type Two Diabetes Mellitus Patients Regarding Diabetic Foot at Koja Regional Hospital in June 2023 - Tamba, Ernawaty; Bo, Alexandra Giacintya Bulan; Hamka, Aldo Muhammad; Mustamu, Swesty Bian; Suryawati, Esther (Jurnal MedScientiae, 2023)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. In the Southeast Asia region, Indonesia is ranked 3rd with a prevalence of 11.3%. Previous studies have shown that the level of knowledge and behavior of type 2 diabetes mellitus patients regarding diabetic foot is still inadequate. This study aims to describe the level of knowledge and behavior of patients with type 2 diabetes mellitus regarding diabetic foot. The research design is descriptive with a cross-sectional approach. The reachable population for this study were all type two diabetes mellitus patients at Koja Hospital who the researchers could meet when conducting the study in June 2023. The sampling technique used was purposive sampling with a sample size of 40 patients. The research subjects were 40 people with type 2 Diabetes Mellitus. The results showed that in terms of knowledge, 50% of sufferers had a high level of knowledge. However, negative behavior is more dominant with a percentage of 57.5%. Although the level of knowledge and type two diabetes mellitus patients about diabetic feet at Koja Hospital in June 2023 is still high, patient behavior is still low, so it is necessary to train and empower health service providers to deliver adequate health messages regarding the prevention of diabetic feet